T Cells That React to the Immunodominant Leishmania major LACK Antigen Prevent Early Dissemination of the Parasite in Susceptible BALB/c Mice - Schilling, Sabrina (American Society for Microbiology, 2001)
Susceptibility of BALB/c mice to Leishmania major depends on the early production of IL-4 by CD4(+) T cells which react to the parasite LACK antigen. Here, we show that LACK-specific cells are rapidly recruited to the site of infection and favor the early dissemination of L. major to the internal organs.